Aktivitas Antioksidan Pada Temulawak (Curcuma xanthorrhiza Roxb.) Dan Jahe Merah (Zingiber officinale var Rubrum) - Fadila, Riska Intan; Iqbal, Muhammad; Triyandi, Ramadhan; Rahayu, Ihsanti Dwi (Medula, 2024)
Temulawak (Curcuma xanthorrhiza Roxb.) or Javanese turmeric is one of the medicine plants from Indonesia, which contains curcuminoid and xanthorrhizol. These compounds have large biological activity, such as antioxidant capacity. The location of this plant grows, affects the variance of the active compound which causes the changes in its activity. This study aims to evaluate antioxidant capacity, total phenolic, and total flavonoid content (TPC and TFC) of the sample collected from different markets, and to classify the samples into different culsters with chemometric techniques. The antioxidant capacity is determined by using DPPH radical scavenging assay. Red ginger (Zingiber officinale var. Rubrum) is a spice plant as well as a plant that functions as a raw material for medicines. In the health sector, red ginger contains compounds that are antioxidants, one of which is phenol compounds. The phenolic compounds present in the red ginger rhizome have the potential to prevent hemolysis and inhibit free radical oxidation reactions in the body. Red ginger (Zingiber officinale var. Rubrum) is a spice plant as well as a plant that functions as a raw material for medicines. In the health sector, red ginger contains compounds that are antioxidants, one of which is phenolic compounds. The phenolic compounds in red ginger rhizomes have the potential to prevent hemolysis and inhibit the process of free radical oxidation in the body. The phenolic compounds in red ginger rhizomes have the potential to prevent hemolysis and inhibit the process of free radical oxidation in the body. Apart from that, red ginger rhizome contains gingerol which has antioxidant, antibacterial, anti-inflammatory, anticarcinogenic, antimutagenic and antitumor activity.